Synthesis, Structure, and Photophysical Properties of Yellow-Green and Blue Photoluminescent Dinuclear and Octanuclear Copper(I) Iodide Complexes with a Disilanylene-Bridged Bispyridine Ligand - Toyotaka Nakae (MDPI AG, 2021)
The synthesis, structural, and photophysical investigations of CuI complexes with a disilanylene-bridged bispyridine ligand 1 are herein presented. Dinuclear (2) and ladder-like (3) octanuclear copper(I) complexes were straightforwardly prepared by exactly controlling the ratio of CuI/ligand 1. Single-crystal X-ray analysis confirmed that dinuclear complex 2 had no apparent π…π stacking whereas octanuclear complex 3 had π…π stacking in the crystal packing. In the solid state, the complexes display yellow-green (λem = 519 nm, Φ = 0.60, τ = 11 µs, 2) and blue (λem = 478 nm, Φ = 0.04, τ = 2.6 µs, 3) phosphorescence, respectively. The density functional theory calculations validate the differences in their optical properties. The difference in the luminescence efficiency between 2 and 3 is attributed to the presence of π…π stacking and the different luminescence processes.